Metabolic responses to acute physical exercise in young rats recovered from fetal protein malnutrition with a fructose-rich diet - Cambri, Lucieli T. [UNESP]; de Araujo, Gustavo G. [UNESP]; Ghezzi, Ana C. [UNESP]; Botezelli, Jose D. [UNESP]; Mello, Maria A. R. [UNESP] (Biomed Central Ltd., 2011)
Background: Malnutrition in utero can program the fetal tissues, making them more vulnerable to metabolic disturbances. Also there is association between excessive consumption of fructose and the development of metabolic syndrome. However, there is little information regarding the acute effect of physical exercise on subjects recovered from malnutrition and/or fed with a fructose- rich diet. The objective of this study was to evaluate the metabolic aspects and the response to acute physical exercise in rats recovered from fetal protein malnutrition with a fructose- rich diet.Methods: Pregnant Wistar rats were fed with a balanced (B) diet or a low-protein (L) diet. After birth and until 60 days of age, the offspring were distributed into four groups according to the diet received: B: B diet during the whole experiment; balanced/fructose (BF): B diet until birth and fructose- rich (F) diet afterwards; low protein/balanced (LB): L diet until birth and B diet afterwards; low protein/fructose (LF): L diet until birth and F diet afterwards.Results: The excess fructose intake reduced the body weight gain, especially in the BF group. Furthermore, the serum total cholesterol and the LDL cholesterol were elevated in this group. In the LF group, the serum total cholesterol and the muscle glycogen increased. Acute physical exercise increased the serum concentrations of glucose, triglycerides, HDL cholesterol and liver lipids and reduced the concentrations of muscle glycogen in all groups.Conclusion: An excess fructose intake induced some signs of metabolic syndrome. However, protein malnutrition appeared to protect against the short term effects of fructose. In other hand, most responses to acute physical exercise were not influenced by early malnutrition and/or by the fructose overload.
Keywords: low protein; nutritional recovery; metabolic syndrome; metabolism; physical exercise; maximal lactate steady-state